Itupale Ewi Odun Oba ni awon Ilu Ajorukomo-Owu (An Examination of Oba Festival's Poetry Inowu Name-Related Towns - Bakare, Yinusa Adeoye (2015)
This study examined the poetry of Oba festivals in Owu name-related towns, by focusing on the sociology, dispersal and interrelationship of the Owu name-related towns in Yorubaland. It also conducted a contrastive analysis of the poetry. This was with a view to identifying the similarities and differences in the poetry and elucidating the sociological background and the effects of the Yoruba Civil War of 1821-1826 on the oneness of the Owu people.